Prediction of Microemulsion Electrokinetic Chromatographic Migration Indices from Molecular Structure - R. Hadjmohammadi, Mohammad; Safa, Fariba (Asian Journal of Chemistry, 2016)
A quantitative structure-migration relationship study was performed to develop a predictive model correlating 33 molecular structures with their migration indices (MI) in microemulsion electrokinetic chromatography. A high quality model (R = 0.992, standard error of estimate = 0.199) was generated using only calculated descriptors and multiple linear regression techniques. The cross-validation procedure results showed good predictive ability of the model (R2cv = 0.905). The results of the study indicated that a five-parameter equation can be utilized for prediction of migration indices of compounds for which there are no empirical MI values.